Effective marker placement for functional identification of the centre of rotation at the hip - Kratzenstein, S.; Kornaropoulos, E.I.; Ehrig, R.M.; Heller, M.O.; Pöpplau, B.M.; Taylor, W.R. (Gait & posture, 2012)
► Assessment of thigh marker positions to find optimal cluster for CoR determination. ► Functional CoR determination using SCoRE and wOCST: in vivo. ► 6 areas for marker placement were determined to provide optimal information. ► Targeted marker placement contributes towards precise determination of CoR. The accuracy and precision of quantifying musculoskeletal kinematics, and particularly determining the centre of rotation (CoR) at the hip joint, using skin marker based motion analysis is limited by soft tissue artefact (STA). We posed the question of whether the contribution of individual markers towards improving the precision of the functional joint centre using marker based methods could be assessed, and then utilised to allow effective marker placement for determination of the CoR at the hip. Sixty-three retro-reflective skin markers were placed to encompass the thighs of seven healthy subjects, together with a set of sixteen markers on the pelvis. The weighted optimal common shape technique (wOCST) was then applied to determine the weighting, or importance, of each marker for identifying the centre of rotation at the hip. The markers with the highest weightings over all subjects and measurements were determined that identified the HJC with the highest precision. The use of six markers in selected regions (two anterior, two lateral and two posterior) allowed the HJC to be determined with a similar precision to the complete set of 63 markers, with the determined regions predominantly distant from the hip joint, excluding areas associated with the bellies of large muscles and therefore large motion artefact from muscle activity. The novel approach presented here allows an understanding of each marker's contribution towards a precise joint determination, and therefore enables the targeted placement of markers for reliable assessment of musculoskeletal kinematics.